Ecology and policy for exclusive breastfeeding in Colombia: a proposal (Colombia Medica, 2012)
Introduction: Breastfeeding promotion is one of the most important strategies against infant mortality and to control child undernourishment. Despite policies and plans to promote and protect breastfeeding in Colombia, its practice is low and its duration is short. Objective: To propose an ecology framework to interpret and incorporate contextual, interpersonal, and individual factors associated with the practice of breastfeeding and duration. Thereby, the plans and policies addressed to promote and protect breastfeeding in Colombia could be reinforced. Conclusions: To implement an ecology framework for Breastfeeding in Colombia, it is necessary to identify the effect of contextual factors in the biggest cultural regions of Colombia, to recognize the limitations of Infant-Friendly Hospital Initiatives to improve exclusive breastfeeding duration, to execute prospective studies in order to identify factors associated with breastfeeding duration, to design and implement plans and policies based on comprehensive planning strategies of healthcare interventions, to develop appropriate and cost-effective extra-institutional strategies aimed at prolonging the duration of breastfeeding, and to implement more reliable breastfeeding surveillance systems.